2011
DOI: 10.1021/nl202767h
|View full text |Cite
|
Sign up to set email alerts
|

Top-Gate ZnO Nanowire Transistors and Integrated Circuits with Ultrathin Self-Assembled Monolayer Gate Dielectric

Abstract: A novel approach for the fabrication of transistors and circuits based on individual single-crystalline ZnO nanowires synthesized by a low-temperature hydrothermal method is reported. The gate dielectric of these transistors is a self-assembled monolayer that has a thickness of 2 nm and efficiently isolates the ZnO nanowire from the top-gate electrodes. Inverters fabricated on a single ZnO nanowire operate with frequencies up to 1 MHz. Compared with metal-semiconductor field-effect transistors, in which the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 30 publications
7
98
0
2
Order By: Relevance
“…If the semiconductor deposition is performed at lower temperatures ( 150 C), also PES foils (T G around 200 C) can be utilized. 226 In an attempt to reduce the substrate cost, especially when cost-effective high throughput fabrication processes are targeted, less expensive (but also less thermally resistance) polymer substrates like PEN 190,[195][196][197]227,228 and PET 76,194,229,230 have been employed. Additionally, the use of paper substrates for flexible solution-processed ZnO TFTs has been investigated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the semiconductor deposition is performed at lower temperatures ( 150 C), also PES foils (T G around 200 C) can be utilized. 226 In an attempt to reduce the substrate cost, especially when cost-effective high throughput fabrication processes are targeted, less expensive (but also less thermally resistance) polymer substrates like PEN 190,[195][196][197]227,228 and PET 76,194,229,230 have been employed. Additionally, the use of paper substrates for flexible solution-processed ZnO TFTs has been investigated.…”
Section: Methodsmentioning
confidence: 99%
“…In general, two approaches can be used to solution-deposit metal oxide semiconducting materials: 236 (A) The material is first synthesized and tailored into nanoparticles, nanorods, or nanowires. 76,190,226,227,230,231,238 These nano-scaled shapes are then dispersed in suitable solvents and subsequently deposited and dried. (B) Alternatively, the precursor solution is first deposited and then converted to the final metal oxide semiconducting material, most commonly via thermal annealing at temperatures in the range of 200 to 500 C, or alternatively via UV irradiation.…”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…25−32 Examples of SAM-functionalized ZnO nanostructures include nanorods modified either with carboxyalkylphosphonic acids (HOOC-(CH 2 ) n P(O)(OH) 2 (n = 2, 9)) for biosensing 25 or with C60-functionalized phosphonic linkers for photonic devices 26 and nanowire-based ZnO field-effect transistors (FET) which use long-chain alkylphosphonic acids as gate dielectrics. 27 Despite various studies reported on a wide range of successful anchoring approaches, issues regarding preferred anchoring modes (monodentate, bidentate, tridendate, bridging bidentate, etc.) of phosphonic acids on ZnO and the role of a second reactive group (i.e., a carboxylic group) are still a matter of controversial interpretations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Спектр функциональных материалов и технологий современной твердотельной микро-и наноэлектроники непрерывно расширяется [1][2][3][4][5][6][7][8][9]. При этом технологи-ческие подходы самоорганизации снизу-вверх (bottomup design), к которым относятся химические и элек-трохимические методы синтеза наноструктурированных объектов, интересны не только с точки зрения формиро-вания резисторов, диодов, транзисторов и электронных устройств на их основе, обладающих видоизмененными параметрами или усовершенствованными характеристи-ками благодаря, например, использованию широкозон-ных полупроводниковых материалов.…”
Section: Introductionunclassified
“…При этом технологи-ческие подходы самоорганизации снизу-вверх (bottomup design), к которым относятся химические и элек-трохимические методы синтеза наноструктурированных объектов, интересны не только с точки зрения формиро-вания резисторов, диодов, транзисторов и электронных устройств на их основе, обладающих видоизмененными параметрами или усовершенствованными характеристи-ками благодаря, например, использованию широкозон-ных полупроводниковых материалов. Не менее актуаль-ным направлением является создание наноэлектронных приборов с особыми параметрами, в частности с ха-рактеристиками, обусловленными туннельными эффек-тами [7][8][9]. Среди них классический туннельный диод Эсаки (Esaki tunnelling diode) и его модификация -обращенный диод (backward diode) выделяются таки-ми преимуществами квантовых приборов, как высокая скорость переключения и низкое энергопотребление одновременно со способностью работать при комнатной температуре.…”
Section: Introductionunclassified